Anti-inflammatory effects of dopamine on microglia and a D1 receptor agonist ameliorates neuroinflammation of the brain in a rat delirium model. (February 2023) - Nishikawa, Yuki; Choudhury, Mohammed E.; Mikami, Kanta; Matsuura, Taisei; Kubo, Madoka; Nagai, Masahiro; Yamagishi, Satoru; Doi, Tomomi; Hisai, Manami; Yamamoto, Haruto; Yajima, Chisato; Nishihara, Tasuku; et al.
Abstract: Microglia play a central role in neuroinflammatory processes by releasing proinflammatory mediators. This process is tightly regulated along with neuronal activities, and neurotransmitters may link neuronal activities to the microglia. In this study, we showed that primary cultured rat microglia express the dopamine (DA) D1 receptor (D1R) and D4R, but not D2R, D3R, or D5R. In response to a D1R-specific agonist SKF-81297 (SKF), the cultured microglia exhibited increased intracellular cAMP levels. DA and SKF suppressed lipopolysaccharide (LPS)-induced expression of interleukin-1β (IL-1β) and tumor necrosis α (TNFα) in cultured microglia. Microglia in the normal mature rat prefrontal cortex (PFC) were sorted and significant expression of D1R, D2R, and D4R was observed. A delirium model was established by administering LPS intraperitoneally to mature male Wistar rats. The model also displayed sleep-wake disturbances as revealed by electroencephalogram and electromyogram recordings as well as increased expression of IL-1β and TNFα in the PFC. DA levels were increased in the PFC 21 h after LPS administration. Increased cytokine expression was observed in sorted microglia from the PFC of the delirium model; however, TNFα, but not IL-1β expression, was abruptly decreased 21 h after LPS administration in the delirium model, whereas DA levels were increased. A D1R antagonist SCH23390 partially abolished the TNFα expression change. This suggests that endogenous DA may play a role in suppressing neuroinflammation. Administration of the DA precursor L-DOPA or SKF to the delirium model rats inhibited the expression of IL-1β and TNFα. The simultaneous administration of clozapine, a D4R antagonist, strengthened the suppressive effects of L-DOPA. These results suggest that D1R mediates the suppressive effects of LPS-induced neuroinflammation, in which microglia may play an important role. Agonists for D1R may be effective for treating delirium. Graphical abstract: Image 1 Highlights: Rat microglia express dopamine receptors in vitro and in vivo. The dopamine D1 receptor (D1R) mediates elevation of intracellular cAMP levels and anti-inflammatory actions. A rat delirium model was prepared by intraperitoneal administration of LPS. The delirium model exhibited sleep disturbances and increased IL-1β and TNFα expression. DA suppressed cytokine expression in rat brains of the delirium model through D1R.